Implementasi Model PBL pada Materi Pengukuran Bangun Datar untuk Mengetahui Aktivitas dan Hasil Pembelajaran Siswa Kelas IV - Ai Lisnawati; Nur Laeli Asyahidah; Ridha Haifarashin; Yeyen Sormin; Komariah Komariah (Journal on Education, 2023)
This teaching activity aims to improve Mathematics learning outcomes in the material Circumference and Area of Squares and Rectangle through the application of the Problem Based Learning model in class IV SDN Majasetra 02. The research method used is qualitative methods. then the researcher also explored the research information from the observations by conducting interviews with the class 4 teacher and accompanied by the implementation of teaching practices in class 4. The research was conducted in one of the elementary schools, namely SDN Majasetra 02 which is in Kp. manirancan, Majasetra, Kec. Majalaya, Kab. Bandung Province West Java. Interviews and documentation were conducted to obtain accurate information about the themes studied. problems and difficulties that occur during learning, namely the teacher has to teach with 64 students in 1 class accompanied by class conditions that are not conducive and some children who do not memorize multiplication and problems that often occur such as students whdid not bring a tool to measure, namely a ruler so that the measurement process was hampered by time (a friend who did not carry a ruler took turns with a friend who brought a ruler). then researchers carry out teaching and learning activities with the PBL model.